User education and information retrieval skills as determinants of library information resources utilisation by distance learning students of University of Ibadan, Nigeria (2015)
The study examined user education and information retrieval skills as determinants of library information resources utilisation by Distance Learning students of University of Ibadan, Nigeria. It is expected of users to effectively utilize library information resources in order to fulfill the requirements of their academic pursuit. For this to be done, it is the library's responsibility to provide user education and better services so that information sources, services and resources are well utilised by the users. Primary data were obtained from 131 respondents using the multistage sampling technique, by means of structured questionnaire. Four research questions and three hypotheses were drawn and answered. Data were analysed using frequency counts and percentages for the research questions while regression and correlation analyses were used to test the hypotheses with the aid o f SPSS Version 21. The study revealed that the major user education programmes available in the University library are talk and orientation as well as library demonstration and ICT training. Majority of the respondents possessed good information retrieval skills concerning their research needs. The major factors militating against the utilisation of library information resources by the students are lack of well equipped library and inadequate ICT infrastructure. User education or students' information retrieval skills have no significant influence on utilization of library information resources. The study further showed there was no significant joint influence of the independent variables on the dependent variable. In view of the foregoing, it is recommended that concerted efforts should be made by the library management to re-orientate its user education programmes so that the imparted skills would facilitate efficient utilization of the library information resources.